DIGITAL ECONOMY AND RECRUITMENT POTENTIAL: STRATEGICAL INTERCONNECTION AND PROSPECTS - G. Yu. Peshkova; А. Yu. Samarina (Russian State Vocational Pedagogical University, 2018)
Introduction. Nowadays, information technologies are developing rapidly. This process affects practically all spheres of life and causes the need of system technological revolutions and modern methods of data processing. A process of digitalisation inevitably changes the structure of population employment and the educational environment as being provider of new HR-recourses.The aims of the research were to identify the problems of the digitalization policy in Russia and to formulate possible solutions.Methodology and research methods. The methods of theoretical investigation were used: abstraction, synthesis, analysis and generalisation.Results. The interaction of education systems and science in the field of preparation of HR-recourses at the stage of digital modernisation of the Russian economy is considered. The impact of digitalisation on vacancies and competences needed and the level of preparedness of Russia for the new technological mode are analysed. The perspective directions of higher education and recruitment policy of enterprise and the whole state are identified. The authors have come to the conclusion that rational recruitment policy is an essential part of Russian economy's digitalisation. The efficiency of realisation of this strategy requires systembased approach to the organisation of staff training for the enterprises in actively changing economic conditions. HR management has become an extremely important element of this system. It is impossible to manage with such digitalization risks as structural unemployment and - at the same time - deficit of highly-qualified specialists without paying attention to what HR-market requires.Scientific novelty. The originality of digital economy is in its optimising effect on production and consumption possible because of operativeness and consolidation of information and computing systems. There has appeared an opportunity to manage socio-economic processes systematically. The necessity of structural changes in HR-market is proved. Moreover, high schools should head the process of overcoming the expected structural unemployment caused by new technologies appearing, i.e. they provide high-quality education of specialised competencies necessary for workers, in particular. Universities must not wait for the government to work out and present new standards and recommendations. On the contrary, high schools ought to independently and urgently initiate the organisation of competitive experts training and to form innovative methods of education of new specialists by cooperating with business sphere and taking examples of digital leaders. To sum up, sensible approach to educational policy can solve the problem of balancing the HК-market and prevent social disturbance.Practical significance. On the example of activity of separate higher education institutions, the ways and models of functioning of the higher school are shown according to economic tendencies.